Evaluation of Recombinant Human Factor IX: Pharmacokinetic Studies in the Rat and the Dog - Keith, James C, Jr; Ferranti, Thomas J; Misra, Bibhu; Frederick, Thomas; Rup, Bonita; McCarthy, Kyle; Faulkner, Robert; Bush, Larry; Schaub, Robert G (Thrombosis and Haemostasis, 1995)
The pharmacokinetics of intravenously administered recombinant human factor IX (rhFIX) were studied in Sprague-Dawley rats and Beagle dogs. Rats received rhFIX (50 IU/kg once daily) for 28 days, and the plasma half-life was 5 h. Anti-Human Factor IX serum antibody levels were found in only 1 of 12 rats. The pharmacokinetic profiles of rhFIX or Mononine™, a purified human plasma-derived factor IX, after single 100 IU/kg IV doses in dogs, were similar. Peak plasma concentrations of rhFIX and Mononine™ were 4–5 μg/ml. The mean plasma half-lives were 13.2 ± 1.6 h for rhFIX and 13.3 ± 1.6 h for Mononine™. Dogs also received rhFIX (40 IU/kg IV, daily) for 28 days or Mononine™ (40 IU/kg IV daily) for 14 days. Anti-human Factor IX serum antibody levels were determined for each compound. Pharmacokinetic half-lives decreased in these treated dogs which developed antihuman Factor IX antibodies. The antibody responses in 28 day rhFIX (40 IU/kg) dogs were similar to 14 day Mononine™ (40 IU/kg) dogs.